(untitled) (Journal of International Studies, 2020)
Against the present-day rhetorical backdrop of globalisation, and the apparently â€œrevolutionaryâ€ nature of information technology, the following paper strives to recount and reconsider the Indian experience of economic liberalisation in the thirty-year period from the introduction of economic liberalisation and deregulatory reform in 1966, to the fall of the Narasimha Congress government in the general elections of 1996. Particular attention is paid to the role of the state in the context of post-colonial India, and how Congress (I) under the leadership of Indira Gandhi introduced economic liberalisation, with the intention of easing poverty, to such an extent that by the end of the 1980s liberalisation, under the banner of New Economic Policy, had allowed India to realise unprecedented economic growth. The legacies of Indiaâ€™s economic liberalisation, however, deserve careful analysis. Economic growth engendered by liberalisation led to India becoming deeply indebted to foreign creditors, and would prove itself to be unsustainable. So much so that by the time Narasimha Rao came to power, in June 1991, India was on the verge of financial crisis, and was forced to seek IMF assistance. Under the auspices of the green revolution and then economic liberalisation, IMF and World Bank tutelage appeared to have sharpened the divisions amongst Indian society to such an extent that the Indian polity was in danger of failure or partial collapse. Given the magnitude and nature of Indiaâ€™s socio-economic problems, perhaps lessons could have been learnt from the example of Japan, and how it extricated itself from an externally driven agenda of economic liberalisation.